Protection Systems in the Integration of Renewable Energy Sources in City Power Supply (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article addresses the issues related to the protection systems of integrated microgrids, which ensure uninterrupted and high quality power supply to all types of electrical consumers connected to the city power supply system. It elaborates on the technical challenges in microgrids, abnormal operating conditions in the power supply, and potential faults. The analysis highlights both internal and external factors that must be considered when applying protection systems for microgrids supplying electrical energy to city areas. Additionally, recommendations have been developed regarding optimal protection systems for city power supply microgrids